Feminist Legal Critique of Child Marriage Dispensation Practices in Indonesian Religious Courts - Bambang Adji Pamungkas (JUSTISIA GLOBAL EDUKASI, 2026)
Although Indonesia has raised the minimum legal age of marriage to nineteen years for both men and women, the continued prevalence of marriage dispensation applications raises concerns regarding the effectiveness of legal reform in preventing child marriage. This article critically examines marriage dispensation practices in Indonesian Religious Courts through the lens of feminist legal theory. Employing normative legal research and qualitative analysis of court decisions, legislation, and judicial considerations, the study explores how judges interpret and apply legal standards when granting marriage dispensations. The findings indicate that judicial reasoning frequently prioritizes social, cultural, and familial considerations over the protection of children’s rights and gender equality principles. In many cases, pregnancy, family pressure, and concerns about social stigma become dominant factors influencing judicial decisions. Such practices risk reproducing structural gender inequalities and undermining the objectives of child protection legislation. The article argues that the persistence of child marriage cannot be understood solely as a legal issue but must be analyzed within broader socio-cultural and patriarchal contexts that shape judicial attitudes and institutional practices. Furthermore, the study highlights inconsistencies in judicial interpretations and the absence of clear criteria for assessing the best interests of the child. By offering a feminist legal critique, this article contributes to scholarly discussions on child rights, gender justice, and judicial reform. It recommends strengthening judicial guidelines, enhancing gender-sensitive legal training, and adopting a rights-based approach that prioritizes children's welfare and long-term development outcomes in marriage dispensation proceedings.